Efektivitas Program Sekolah Keluarga di Kota Bukittinggi - Putri Zahira; Dadang Mashur (Pencerah, 2021)
The Family School Program is a form of public service innovation that is motivated by the rise of immoral cases that cause high numbers of social problems in Bukittinggi City. This program is present to improve the quality of family resilience through strengthening of eight family functions. However, in the implementation of this program, there are still some problems that become obstacles to the implementation of the program. This research aims to find out the effectiveness of the implementation of the Family School Program organized by the Bukittinggi City P3APPKB Office. The theoretical concept that researchers use is the theory of effectiveness by Sutrisno with five indicators, namely program understanding, on target, on time, achievement of goals, and real change. Research uses qualitative research methods, with data collection techniques based on interviews, observations and documentation. The results of the research found that the implementation of the Family School Program has not been implemented effectively, because on two indicators, namely on target and the achievement of goals do not run according to the goals behind the formation of the program. In addition, the obstacles faced by the P3APPKB Office on the implementation of the program are the lack of number of picket officers in the implementing unit and the lack of public interest to follow the program among men.